Remote sensing and geographic information systems for inflow estimation in reservoir operations - Sarmiento, Czar Jakiri Soriano (2010)
In managing a multipurpose dam, knowledge of water inflow or the amount of water entering the reservoir is essential in planning and scheduling discharges for optimal power production and irrigation supply, and in flood control. Utilization of satellite imagery improves inflow estimates provided by digital spatial data rather than calculations from drawn maps. Satellite imagery yields measurements over an area are obtained instead of extrapolations from point measurements.